Relationship between paramagnetic rim lesions and slowly expanding lesions in multiple sclerosis. (March 2023) - Calvi, Alberto; Clarke, Margareta A; Prados, Ferran; Chard, Declan; Ciccarelli, Olga; Alberich, Manel; Pareto, Deborah; Rodríguez Barranco, Marta; Sastre-Garriga, Jaume; Tur, Carmen; Rovira, Alex; Barkhof, Frederik
Background: Magnetic resonance imaging (MRI) markers for chronic active lesions in MS include slowly expanding lesions (SELs) and paramagnetic rim lesions (PRLs). Objectives: To identify the relationship between SELs and PRLs in MS, and their association with disability. Methods: 61 people with MS (pwMS) followed retrospectively with MRI including baseline susceptibility-weighted imaging, and longitudinal T1 and T2-weighted scans. SELs were computed using deformation field maps; PRLs were visually identified. Mixed-effects models assessed differences in Expanded Disability Status Scale (EDSS) score changes between the group defined by the presence of SELs and or PRLs. Results: The median follow-up time was 3.2 years. At baseline, out of 1492 lesions, 616 were classified as SELs, and 80 as PRLs. 92% of patients had ⩾ 1 SEL, 56% had ⩾ 1 PRL, while both were found in 51%. SELs compared to non-SELs were more likely to also be PRLs (7% vs. 4%, p = 0.027). PRL counts positively correlated with SEL counts (ρ= 0.28, p = 0.03). SEL + PRL + patients had greater increases in EDSS over time (beta = 0.15/year, 95% confidence interval (0.04, 0.27), p = 0.009) than SEL+PRL-patients. Conclusion: SELs are more numerous than PRLs in pwMS. Compared with either SELs or PRLs found in isolation, their joint occurrence was associated with greater clinical progression.